Crop-livestock integration systems mitigate soil compaction and increase soybean yield - Jordaanny Danyelly Pereira Lima; José Fausto Guimarães Silva; Adalto Jose de Souza Linhares; Katia Aparecida de Pinho Costa; Camila Jorge Bernabé Ferreira; Eduardo da Costa Severiano (Acta Scientiarum: Agronomy)
The use of integrated agricultural production systems has been expanded due to the multiple functions they perform. Although soil structural studies have elucidated the relationship of these systems with plant development, adjustments are needed to incorporate the diversity of management systems employed. Thus, the hypothesis of this study was that integrated cropping systems mitigate soil structural degradation and increase the agronomic performance of crops. The objectives of this study were to evaluate the biological soil loosening potential containing paiaguás grass and the effectiveness of integrated systems in promoting the agronomic performance of soybean plants and to model the least limiting water range (LLWR) considering the adopted management regimes. An experiment was performed based on a randomized block and split-plot design. In the plots, the traffic intensity (0, 2, 10, and 30 passes of an agricultural tractor. In the subplots, soybean cultivation was performed under the three management systems (simple: monoculture grains; integrated: intercropping between grass and grains; and pasture in monoculture). The following soil physical quality indicators were determined: bulk density (Bd) and LLWR; these indicators are related to phenological development attributes and soybean productivity. The integrated agricultural production systems promoted biological soil loosening and improved soybean yield. The use of Paiaguás grass in monoculture enhanced edaphic benefits and enabled greater grain production compared to grain monocropping. The least limiting water range was an efficient parameter for modeling the physical behavior of the soil, and the application of the LLWR was improved by considering penetration resistance reference values specific to each management system. Our results highlight the soundness of using the LLWR in evaluating the response of soybean to physical changes in soil due to compaction, and the reference values for penetration resistance contribute to greater accuracy in the LLWR and the physical diagnosis of soil properties.